Al-Wahy fi Hayat al-Basyar - Syahlan, Abdul Aziz (Research and Development Institution, Darussalam Institute for Islamic Studies, 2016)
Each Divine Message has two sides: one doctrinal (dealing with faith’s dogmas) and another practical (preaching the practice of some rituals). Faith reminds Man of Allah (God) and of the Hereafter, and aims to strengthen man’s natural believing predisposition against deceitful temptation and the wicked forces of evil that strive continuously to push him to reject faith and to surrender to impiety. These forces try to deceive man into believing that, by this impiety and this rejection of faith, he can free himself from any constraints imposed upon him by religion, and that in the absence of these constraints, he will find his peace and freedom. But all this is but an illusion. It has been known that excessively indulging in the pleasures of life and its delights leads to boredom, and boredom, as it is well known, can be a form of constraining bondage. Opulence as well as poverty are both earthly severe trials which befall both believers and unbelievers. The common wisdom would have it that the worst constraints that a person can be subjected to, whilst outside Allah’s path, are those that will make life become so bitter as to be bitterness itself. Moreover, whoever has not tasted the sweetness of faith, reaps for himself only life’s worries and futilities, which will leave him be a prey to disgust and boredom.